A Highly Stretchable Liquid Metal Polymer as Reversible Transitional Insulator and Conductor - Wang, Hongzhang (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.